SUBSTANCINIAI IR PROCEDŪRINIAI PRAKTINIO RACIONALUMO ASPEKTAI. - Norkus, Zenonas (Problems / Problemos, 2008)
The article discusses the distinction between substantive and procedural rationality made by Herbert Simon, which has provided the conceptual framework for the empirical research on the boundaries of human rationality. In this research, two approaches with a different understanding of heuristics for cognition and choice are distinguished. In the first approach (David Kahneman, Amos Tversky), heuristics is interpreted as a source of the pathologies in human rationality. In the second (Gerd Gigerenzer), they are conceived as a means for an effective simulation of substantive rationality, making human behaviour ecologically rational. Discussing the reasons for this Janus-faced duplicity of heuristics, some ambiguities in the distinction between the procedural and substantive rationality are disclosed. This distinction may mean (1) the difference between the process and the product of information processing; (2) the distinction between correct but unpracticable alghoritms and incorrect but practical heuristics in information processing itself, and (3) between the form and the content (substance) in the problem solving behaviour. Another source of the problems with this distinction is reflexivity of the knowledge about rationality, i. e. the impact of the theories of rationality on their object (human rationality).